2019
DOI: 10.1002/hep4.1358
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Platelet‐Derived Extracellular Vesicles in Liver Physiology and Disease

Abstract: Beyond their role in hemostasis, platelets are proposed as key mediators of several physiological and pathophysiological processes of the liver, such as liver regeneration, toxic or viral acute liver injury, liver fibrosis, and carcinogenesis. The effects of platelets on the liver involve interactions with sinusoidal endothelial cells and the release of platelet‐contained molecules following platelet activation. Platelets are the major source of circulating extracellular vesicles, which are suggested to play k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 139 publications
(266 reference statements)
0
22
0
Order By: Relevance
“…Thrombocytopenia is also compensated by the presence of platelet-derived extracellular vesicles (EV); microparticles (0.1–1 μm) which are highly pro-coagulant and contribute to ongoing activation of coagulation ( 23 ). Recently a study by Stravitz et al showed that patients suffering from acute liver failure had an increased amount of these circulating microparticles ( 23 , 24 ).…”
Section: Rebalanced Hemostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia is also compensated by the presence of platelet-derived extracellular vesicles (EV); microparticles (0.1–1 μm) which are highly pro-coagulant and contribute to ongoing activation of coagulation ( 23 ). Recently a study by Stravitz et al showed that patients suffering from acute liver failure had an increased amount of these circulating microparticles ( 23 , 24 ).…”
Section: Rebalanced Hemostasismentioning
confidence: 99%
“…In summary, contrary to the common belief that acute liver failure patients are “autoanticoagulated,” they may be more prone to thrombosis rather than bleeding. There is a combination of (a) thrombocytopenia compensated with elevated levels of vWF, factor VIII and reduced ADAMTS-13, (b) a hypofibrinolytic state due to elevated PAI-1 and low plasminogen, and (c) elevated levels of pro-coagulant microparticles that may all lead to an increased risk of thrombosis and worsen outcome ( 23 , 24 ).…”
Section: Rebalanced Hemostasismentioning
confidence: 99%
“…Platelet-derived EVs are primarily characterised by the presence of CD41, CD42b and phosphatidylserine and have been demonstrated to play roles in exercise [27, 28], acute injury [29] and diabetes [30]. Platelet-derived EVs are regarded as the most abundant source of plasma EVs; however, it is unclear as to what proportion of the EV pool they represent, with approximations varying from 50 to 90% [29]. Platelet EV release is calcium dependent and relies on actin cytoskeleton destabilisation [31].…”
Section: Evs As Biomarkers Of Metabolic Diseasementioning
confidence: 99%
“…Furthermore, to add complexity, EVs can also be secreted from other cells and influence liver inflammation. In this regard, some evidence suggests that platelet-derived EVs may have proinflammatory effects in the liver, but this needs further confirmation [39,40]. Finally, it has also been shown that EVs are released from monocytic cells and induce polarization towards the anti-inflammatory M2 phenotype of neighboring naive monocytes by delivering cargo miR-27a, thus contributing to resolution of inflammation [41].…”
Section: Evs and Liver Inflammationmentioning
confidence: 99%